Subdistribution to cox's model for partly interval-censored data with application to aids studies - Elfaki, Faiz Ahmed Mohamed (Asian Research Publishing Network (ARPN), 2015)
In this paper, we consider incomplete survival data that is, partly-interval failure time data where observed data include both exact and interval-censored observation on the survival time of interest. We presented a modification of Fine and Gray (1999) which proposed a class of estimation procedures for semi-parametric proportional hazards regression model for the subdistribution of a competing risks model using the partial likelihood principle and weighting techniques. The method is evaluated using simulation studies and illustrated by AIDS data set.